Treatment modalities of temporamandibular disorders - (:unkn) unknown (My University, 2015)
Temporomandibular eklem (TME), morfolojik olarak kişi den kişiye değişkenlik gösteren bir eklemdir. Temporo mandibular düzensizlik (TMD) terimi çiğneme kasları, temporomandibular eklem ve temporomandibular ekleme komşu dokuların çoğunlukla ağrılı, fizyolojik ve fonksiyon bozukluklarını ifade eder. Yeni tekniklerin bulunması ve özellikle bilgisayar alanındaki gelişmeler, TME anatomisi ve fonksiyonlarını daha iyi değerlendirmemizi sağlamış tır. Diş hekimleri dental müdahaleler esnasında hastalığın bulgularını gözden kaçırmamalıdır. Hastalar sıklıkla artan ağrı ve/veya disfonksiyon nedeniyle tedavi arayışı içinde dirler. Bu derlemede TMD tanı ve tedavisi hakkında bilgi vererek güncel yaklaşımların tanıtılması amaçlanmıştır.

Temporomandibular joint (TMJ), morphologically variable from person to person. Temporomandibular disorders (TMD) refers to the muscles of mastication, Temporomandibular joint and temporomandibular adding adjacent tissues is often painful, refers to the physiological and functional disorders. Discovery of new techniques, and especially computer advances, TMJ Anatomy and function of the evaluation has provided us. Dentists, dental interventions reviewed the findings of the disease during the lessons. Patients are often increased pain and/or are in search of treatment due to dysfunction. In this review the TMD diagnosis and treatment by providing information about the current approach is intended to promote.
Temporomandibular Eklem Rahatsızlıkları Tedavi Yöntemleri
Keywords: Diş Hekimliği